(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
This research presents the effect of fatigue life behavior of aluminum alloy AA 7075 under constant loading amplitude conditions and tested at different temperatures. The prediction of fatigue life using conventional experimental procedures makes the analysis of behavior is real and gives accurate results. The stress-life curves at different temperatures (25, 75, 125, 175 and 225 oC) were estimated. The results for fatigue life at ambient temperature and at elevated temperatures were discussed by the Basquin’s relation, and a decrease in fatigue life cycles was found when increasing the testing temperature. Good agreement has been obtained when comparing the current study results with other available experimental data by other studies. A general proposed model (mathematical expression) was formulated to calculate the fatigue life for aluminum alloy AA 7075 at different temperatures. The proposed mathematical model obtained in this study can be used for decreasing the cost and time of the experimental procedures. Also, the Fatigue Life Reduction Factor (FLRF) was increased with increased of the testing temperature at maximum value of (43.963%) occurred at temperature of 225 °C compared with room temperature when applied stress be equal to 540 MPa.